Harriet Jacobs and Incidents in the life of a slave girl new critical essays - Garfield, Deborah M. ca. 20./21. Jahrhundert; Zafar, Rafia (Cambridge studies in American literature and culture, 1996)
Harriet Jacobs, today perhaps the single-most read and studied black American woman of the nineteenth century, has not until recently enjoyed sustained, scholarly analysis. This anthology presents a far-ranging compendium of literary and cultural scholarship which will take its place as the primary resource for students and teachers of Incidents in the Life of a Slave Girl. The contributors include both established Jacobs scholars such as Jean Fagan Yellin (biographer and editor of the annotated edition of Incidents), Frances Smith Foster, Donald Gibson, and emerging critics Sandra Gunning, P. Gabrielle Foreman, and Anita Goldman. The essays take on a variety of subjects in Incidents, treating representation, gender, resistance, and spirituality from differing angles. The chapters contextualise both the historical figure of Harriet Jacobs and her autobiography as a created work of art; all endeavour to be accessible to a heterogeneous readership